(untitled) (Eurasian Research Bulletin, 2023)
The purpose of this study is to develop an application in the field of medicine based on the perspective of patients in polyclinics of the Republic of Uzbekistan. In the medical field, the software development process has been ongoing since technology has partnered with it. Therefore, the author decided to develop two programs. One is a mobile app and the other is a web app. Two programs for patients. This research is divided into four stages of work. First, it examines the stage of requirements for applications with local polyclinics. Second, determine the program design based on the results of the requirements phase. Third, the user design and programming code are applied to the software prototypes, and there is also a testing phase to find some bugs. At the end of the phase, the final apps will be released and the final version will be the testing phase to make sure the apps work well. The results of the study show that applications perform well with features that match the stage of requirements. The presence of applications can be changed enough to improve functionality.